ISSUES OF DEVELOPING MEDIA AND INFORMATION LITERACY OF THE FUTURE MUSIC TEACHER (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the issues of developing media and information literacy among future music teachers from a scientific and pedagogical perspective. It examines the impact of the digital learning environment, media platforms, audiovisual resources, and modern information technologies on music education. Particular attention is paid to the role of media and information literacy in the professional competence of future music teachers, including the skills of searching for, selecting, verifying, evaluating, and using musical information for appropriate pedagogical purposes. The article also addresses copyright, academic integrity, media ethics, and pedagogical responsibility in working with digital content. Based on the analysis of international and local scholarly sources, the necessity of systematically developing media and information literacy in the process of training music teachers is substantiated, and practical recommendations for improving this area are proposed.